Integrating Lean and Cost of Quality Models to Improve Hospitals’ Financials: A Conceptual Framework - Aoun, Malak; Alaaraj, Hassan (2017)
Measuring the cost of quality in hospitals has been the main concern of quality, finance and accounting managers. It is a complicated task to balance between reducing the cost and providing a high quality service. Thus, hospitals integrate different quality improvement models such as lean and cost of quality to identify the wastes resulted from the cost of poor quality and spot the opportunities for improving the cost of good quality.This study reviews the literature related to these two models and highlights its implementation in the healthcare sector.Hence, a conceptual framework is proposed. One of the main research implications is that accounting and quality assurance teams have to cooperate and share information to reduce undesirable costs and improve the hospital’s financials. However, future studies are encouraged to expand the research empirically to discover hidden costs of quality and implement different improvement quality models to enrich the literature